2019
DOI: 10.1108/ijoem-08-2018-0433
|View full text |Cite
|
Sign up to set email alerts
|

The logics of political business in state-owned enterprises: the case of Indonesia

Abstract: Purpose The purpose of this paper is to illuminate the hidden process of collusion among power holders in state-owned enterprises (SOEs) in an emerging economy, which endures despite comprehensive reforms towards democracy and good governance. Why are mechanisms of checks and balances not functioning in the way they should? Design/methodology/approach The analysis is based on in-depth interviews with board members, executives, politicians, bureaucrats and representatives from auditing boards involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 71 publications
1
15
0
1
Order By: Relevance
“…Therefore, SOE's excellent performance will disappear during the election period. The results of this study are in line with Apriliyanti and Kristiansen (2019) which shows that rent-seeking among political and business elites in the government will hamper the governance and performance of SOE companies. In addition, SOEs are companies that have political connections with the government, so their performance will depend on the strength of their connections (Fisman, 2001;Harymawan & Nowland, 2016;Leuz & Oberholzer-Gee, 2006).…”
Section: Empirical Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, SOE's excellent performance will disappear during the election period. The results of this study are in line with Apriliyanti and Kristiansen (2019) which shows that rent-seeking among political and business elites in the government will hamper the governance and performance of SOE companies. In addition, SOEs are companies that have political connections with the government, so their performance will depend on the strength of their connections (Fisman, 2001;Harymawan & Nowland, 2016;Leuz & Oberholzer-Gee, 2006).…”
Section: Empirical Results and Discussionsupporting
confidence: 85%
“…Sukmadilaga et al (2014) also explained that during the Crisis the government would inject direct subsidies to enable SOEs to maintain their performance. Apriliyanti and Kristiansen (2019) show that rentseeking, collusion and corruption among political and business elites and high-ranking officials in the government detain the reforming of corporate governance of SOEs. Anecdotal evidence shows that the appointments for Ministry of State-owned Enterprises in Indonesia are more political than professional.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…So far, these kinds of studies could not be found in Indonesia. There is a study that studies Indonesian business and political connections but not for SOEs (Apriliyanti & Kristiansen, 2018). They found that the check and balance mechanism is not working in SOEs.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Finally, there is doubt as to whether SOE directors appointed by politicians are able to act in the best interest of the citizen and whether there is the autonomy of such directors to perform their work without political interference (Kuzman et al, 2018). Corrobarating this assertion, Apriliyanti and Kristiansen (2019) observe that SOEs are generally exposed to corruption than their private counterparts because of the potential political interference in board composition as well as in business decisions by politicians and public officials.…”
Section: Introductionmentioning
confidence: 99%